From UTP to AR-C118925, the discovery of a potent non nucleotide antagonist of the P2Y2 receptor - Kindon, Nicholas; Davis, Andrew; Dougall, Iain; Dixon, John; Johnson, Timothy; Walters, Iain; Thom, Steve; McKechnie, Kenneth; Meghani, Premji; Stocks, Michael (Elsevier, 2017)
The G protein-coupled P2Y2 receptor, activated by ATP and UTP has been reported as a potential drug target for a wide range of important clinical conditions, such as tumor metastasis, kidney disorders, and in the treatment of inflammatory conditions. However, pharmacological studies on this receptor have been impeded by the limited reported availability of stable, potent and selective P2Y2R antagonists. This article describes the design and synthesis of AR-C118925, a potent and selective non-nucleotide antagonist of the P2Y2 receptor discovered using the endogenous P2Y2R agonist UTP as the chemical starting point.